2013
DOI: 10.1177/1077558712470565
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Emergency Department Admission Rates Across the United States

Abstract: There were more than 19 million hospitalizations in 2008 from hospital-based emergency departments (EDs), representing nearly 50% of all U.S. admissions. Factors related to variation in hospital-level ED admission rates are unknown. Generalized linear models were used to assess patient-, hospital-, and community-level factors associated with ED admission rates across a sample of U.S. hospitals using Healthcare Cost and Utilization Project data. In 1,376 EDs, the mean ED admission rate, when defined as direct a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
60
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 98 publications
(65 citation statements)
references
References 20 publications
3
60
2
Order By: Relevance
“…The lack of access to primary care physicians in the local community has been found to be associated with higher ED admission rates, as have greater ED volume, trauma designation, metropolitan location, and teaching status. 7,9,23 At the ED level, physicians appear to be strongly influenced by local standards of care in their decision-making as well as by personal attitudes toward risk tolerance and malpractice fear. 7,[24][25][26] One study examining physician level variation in admission rates in adult EDs found a greater than twofold variation in admission rates within single institutions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of access to primary care physicians in the local community has been found to be associated with higher ED admission rates, as have greater ED volume, trauma designation, metropolitan location, and teaching status. 7,9,23 At the ED level, physicians appear to be strongly influenced by local standards of care in their decision-making as well as by personal attitudes toward risk tolerance and malpractice fear. 7,[24][25][26] One study examining physician level variation in admission rates in adult EDs found a greater than twofold variation in admission rates within single institutions.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6] Some of the variation in care may be related to patientlevel differences in clinical presentation as well as to hospital-level factors, such as local availability of primary care physicians, hospital occupancy, or access to certain health care services. [7][8][9] The wide variation in clinical management raises concerns about whether every patient is receiving the optimal care and whether the lack of a standardized approach is contributing to unnecessary health care costs. [10][11][12] Additional testing and treatment have not necessarily been found to correlate with more effective care, improved patient outcomes, or higher patient satisfaction.…”
mentioning
confidence: 99%
“…Recent studies have demonstrated wide variation in admission rates among emergency physicians and across hospitals. [3][4][5] Factors such as risk tolerance and malpractice fear have been identified as important explanatory factors at the physician level. [6][7][8] Patients who are treated and released, but subsequently return with serious causes for chest pain, are a particular concern because patients with "missed" acute myocardial infarction (AMI) have worse outcomes.…”
Section: % Including Both Inpatient Hospital and Observation Statumentioning
confidence: 99%
“…It is estimated that 50% of admissions to hospitals in the United States are initially assessed and treated in EDs. 20 The ED is also the only access point in the U.S. acute health care system available to patients 24 hours per day, 7 days per week. In the United States there is a legal obligation under EMTALA to provide a medical screening examination for an emergency medical condition and treatment until the emergency medical condition is resolved or stabilized to the extent of that hospital's capability (until appropriate transfer), regardless of insurance status or other socioeconomic factors.…”
Section: Characteristics Of Ed Practice Of Ethical Relevancementioning
confidence: 99%